2019
DOI: 10.1088/1361-6463/ab3362
|View full text |Cite
|
Sign up to set email alerts
|

Electrical explosion of aluminum wire for preparation of nanoparticles: an experimental study

Abstract: An experimental study on the characteristics of aluminum wire explosion in ambient gas is carried out. A compact experimental device is built to study the electrical parameters, morphology and size distribution of nanoparticles generated by wire explosion. The typical characteristics are obtained and the influence of the type and pressure of the ambient gas is investigated. The explosion process in argon indicates a longer time for breakdown development and larger deposited energy compared with those in helium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To prepare liquid containing aluminium NPs suspended in vinyl alcohol monomer, an electric exploding wire technique was used (Fan et al, 2020;Alsaad et al, 2021;Tang et al, 2015). This method is considered one of the most environmentally friendly methods for preparing NPs of metallic materials (Tang et al, 2015;Hussein and Kadhem, 2021;Abdulla et al, 2022;Bai et al, 2019;Tanaka et al, 2021;Ghorbani, 2014;Abbass and Kadhem, 2018). To produce Al/PVA films, a plasma jet system was used because it is an easy, inexpensive, and efficient way to produce thin films (Abbass and Kadhem, 2018;Nikiforov et al, 2015;Gencer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To prepare liquid containing aluminium NPs suspended in vinyl alcohol monomer, an electric exploding wire technique was used (Fan et al, 2020;Alsaad et al, 2021;Tang et al, 2015). This method is considered one of the most environmentally friendly methods for preparing NPs of metallic materials (Tang et al, 2015;Hussein and Kadhem, 2021;Abdulla et al, 2022;Bai et al, 2019;Tanaka et al, 2021;Ghorbani, 2014;Abbass and Kadhem, 2018). To produce Al/PVA films, a plasma jet system was used because it is an easy, inexpensive, and efficient way to produce thin films (Abbass and Kadhem, 2018;Nikiforov et al, 2015;Gencer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sindhu et al found that the geometric mean size was smallest in helium ambiance compared to argon and nitrogen gas in both experiment and simulation due to the higher thermal conductivity (cooling rate) of helium [ 12 ]. However, the rapid phase transition of the exploding wire induces surface flashover, which causes incomplete vaporization/atomization, increasing the inhomogeneity of the explosion products [ 13 , 14 ]. Additionally, the development of electro-thermal instability, characterized by periodic striations, can increase the size range of the nanoparticles [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They proposed a nanoparticle formation mechanism that is caused by the condensation of primary particles produced in the early stages of wire electrical explosions. Bai et al [20] studied the electrical explosion characteristics of Al wire in ambient gas and considered that the explosion process in Ar has longer breakdown development time and greater deposition energy than that in He. It can be seen that Ar is more suitable as a protective gas in Al wire electrical explosion, and is more widely used.…”
Section: Introductionmentioning
confidence: 99%